Fieldwork Notes - Muhammad Syafar (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2017)
Gender and Social Assessment (Study of Micro Hydro Power Plants Development based on Local Natural Resources to in Mamasa-West Sulawesi)